Genotype - Proteotype - Phenotype Relationships in Neurodegenerative Diseases - Cummings, J.; Hardy, J.; Poncet, M. (Research and Perspectives in Alzheimer's Disease,, 2005)
Protein misfolding and other abnormalities of protein metabolism are increasingly recognized as central mechanisms in the pathophysiology of neurodegenerative disorders. Amyloid beta protein disturbances in Alzheimer's disease, tau and ubiquitin protein abnormalities in frontotemporal dementias, proteasome and alpha-synuclein disorders in Parkinson's disease and dementia with Lewy bodies comprise central elements in these common neurodegenerative diseases. Improved understanding of role of protein dysmetabolism in neurodegeneration promises to improve diagnoses, facilitate the development of biological markers relevant to disease pathophysiology, and provide tractable therapeutic targets. This Fondation IPSEN conference summary provides an update on the latest advances of the role of protein misfolding in the pathophysiology of neurodegenerative diseases.